Line 9: Line 9:
 
<br>
 
<br>
 
<br>
 
<br>
<math>A = \left(\begin{array}{cccc}4&3\\3&2\end{array}\right)</math>  
+
<math>A = \left(\begin{array}{cc}4&3\\3&2\end{array}\right)</math>  
 
<br>
 
<br>
<math>A^{-1} = \left(\begin{array}{cccc}-2&3\\3&-4\end{array}\right)</math>   
+
<math>A^{-1} = \left(\begin{array}{cc}-2&3\\3&-4\end{array}\right)</math>   
  
 
<br>
 
<br>
  
<math>AA^{-1} = \left(\begin{array}{cccc}4&3\\3&2\end{array}\right)</math><math>\left(\begin{array}{cccc}-2&3\\3&-4\end{array}\right) = </math> <math>\left(\begin{array}{cccc}1&0\\0&1\end{array}\right)</math>  
+
<math>AA^{-1} = \left(\begin{array}{cc}4&3\\3&2\end{array}\right)</math><math>\left(\begin{array}{cc}-2&3\\3&-4\end{array}\right) = </math> <math>\left(\begin{array}{cc}1&0\\0&1\end{array}\right)</math>  
  
 
<br>
 
<br>
 
and
 
and
 
<br>
 
<br>
<math>A^{-1} = \left(\begin{array}{cccc}-2&3\\3&-4\end{array}\right)</math><math>\left(\begin{array}{cccc}4&3\\3&2\end{array}\right) = </math><math>\left(\begin{array}{cccc}1&0\\0&1\end{array}\right)</math>   
+
<math>A^{-1} = \left(\begin{array}{cc}-2&3\\3&-4\end{array}\right)</math><math>\left(\begin{array}{cc}4&3\\3&2\end{array}\right) = </math><math>\left(\begin{array}{cc}1&0\\0&1\end{array}\right)</math>   
  
 
----
 
----
Line 51: Line 51:
 
<h4> 1. Shortcut for determining the inverse of a 2 x 2 matrix </h4>
 
<h4> 1. Shortcut for determining the inverse of a 2 x 2 matrix </h4>
  
<p> If      <math>A = \left(\begin{array}{cccc}a&b\\c&d\end{array}\right)</math>  then the inverse of matrix A can be found using:
+
<p> If      <math>A = \left(\begin{array}{cc}a&b\\c&d\end{array}\right)</math>  then the inverse of matrix A can be found using:
 
<br>
 
<br>
<math>A^{-1} = \frac{1}{detA}\left(\begin{array}{cccc}d&-b\\-c&a\end{array}\right) = \frac{1}{ad - bc}\left(\begin{array}{cccc}d&-b\\-c&a\end{array}\right)</math>
+
<math>A^{-1} = \frac{1}{detA}\left(\begin{array}{cc}d&-b\\-c&a\end{array}\right) = \frac{1}{ad - bc}\left(\begin{array}{cc}d&-b\\-c&a\end{array}\right)</math>
  
 
</p>
 
</p>
Line 67: Line 67:
 
<br>
 
<br>
  
<math>A = \left(\begin{array}{cccc}1&2\\3&4\end{array}\right)</math>
+
<math>A = \left(\begin{array}{cc}1&2\\3&4\end{array}\right)</math>
  
 
<br>
 
<br>
Line 75: Line 75:
 
<br>  
 
<br>  
  
<math>A^{-1} = \frac{1}{-2}\left(\begin{array}{cccc}4&-2\\-3&1\end{array}\right)</math>
+
<math>A^{-1} = \frac{1}{-2}\left(\begin{array}{cc}4&-2\\-3&1\end{array}\right)</math>
  
 
<br>
 
<br>
  
<math>A^{-1} = \left(\begin{array}{cccc}-2&1\\\frac{3}{2}&\frac{-1}{2}\end{array}\right)</math>
+
<math>A^{-1} = \left(\begin{array}{cc}-2&1\\\frac{3}{2}&\frac{-1}{2}\end{array}\right)</math>
  
 
</p>
 
</p>
Line 95: Line 95:
  
 
<p> <b>Example.</b>
 
<p> <b>Example.</b>
 +
  
 
Find A<sup>-1</sup> of  
 
Find A<sup>-1</sup> of  
  
<math>A = \left(\begin{array}{cccc}1&2\\3&4\end{array}\right)</math>
+
<br>
 +
 
 +
<math>A = \left(\begin{array}{cc}1&2\\3&4\end{array}\right)</math>
 +
 
  
  

Revision as of 07:30, 10 December 2012

Inverse of a Matrix

An n x n matrix A is said to have an inverse provided there exists an n x n matrix B such that AB = BA = In. We call B the inverse of A and denote it as A-1. Thus, AA-1 = A-1A = In. In this case, A is also called nonsingular.



Example.

$ A = \left(\begin{array}{cc}4&3\\3&2\end{array}\right) $
$ A^{-1} = \left(\begin{array}{cc}-2&3\\3&-4\end{array}\right) $


$ AA^{-1} = \left(\begin{array}{cc}4&3\\3&2\end{array}\right) $$ \left(\begin{array}{cc}-2&3\\3&-4\end{array}\right) = $ $ \left(\begin{array}{cc}1&0\\0&1\end{array}\right) $


and
$ A^{-1} = \left(\begin{array}{cc}-2&3\\3&-4\end{array}\right) $$ \left(\begin{array}{cc}4&3\\3&2\end{array}\right) = $$ \left(\begin{array}{cc}1&0\\0&1\end{array}\right) $


Theorem 1

The inverse of a matrix, if it exists, is unique

Theorem 2

If A and B are both nonsingular n x n matrices (i.e. invertible), then AB is nonsingular and (AB)-1 = B-1A-1.

Corollary 1

If A1, A2, ..., Ar are n x n nonsingular matrices, then A1A2...Ar is nonsingular an (A1A2...Ar)-1 = Ar-1Ar-1-1...A1-1.

Theorem 3

If A is a nonsingular matrix, then A-1 is nonsingular and (A-1)-1 = A.

Theorem 4

If A is a nonsingular matrix, then AT is nonsingular and (A-1)T = (AT)-1.



Methods for determining the inverse of a matrix

1. Shortcut for determining the inverse of a 2 x 2 matrix

If $ A = \left(\begin{array}{cc}a&b\\c&d\end{array}\right) $ then the inverse of matrix A can be found using:
$ A^{-1} = \frac{1}{detA}\left(\begin{array}{cc}d&-b\\-c&a\end{array}\right) = \frac{1}{ad - bc}\left(\begin{array}{cc}d&-b\\-c&a\end{array}\right) $




Example

$ A = \left(\begin{array}{cc}1&2\\3&4\end{array}\right) $
$ detA = ad - bc = 1 \times 4 - 2 \times 3 = -2 $
$ A^{-1} = \frac{1}{-2}\left(\begin{array}{cc}4&-2\\-3&1\end{array}\right) $
$ A^{-1} = \left(\begin{array}{cc}-2&1\\\frac{3}{2}&\frac{-1}{2}\end{array}\right) $



2. Augmented Matrix Method (Can be used for any n x n matrix)

Use Gauss-Jordan Elimination to transform [ A | I ] into [ I | A-1 ].

$ \left(\begin{array}{ccc|ccc}a&b&c&1&0&0\\d&e&f&0&1&0\\g&h&i&0&0&1\end{array}\right) $


Example. Find A-1 of
$ A = \left(\begin{array}{cc}1&2\\3&4\end{array}\right) $

Alumni Liaison

Abstract algebra continues the conceptual developments of linear algebra, on an even grander scale.

Dr. Paul Garrett